Integrasi Agroforestri dan Sistem Budidaya Lebah Madu (Trigona Sp.) dalam Penguatan Food Estate di Humbang Hasundutan. - Luthfi Hakim; Tito Sucipto; Apri Heri Iswanto; Jajang Sutiawan; Rudi Hartono; Harisyah Manurung; Samsuri Samsuri; Anita Zaitunah; OK Hasnanda Syahputra; Agus Purwoko; Hafizah Arinah; Moehar Maraghiy Harahap; Mariah Ulfa; Ridahati Rambey; Suri Fadhilla; Arida Susilowati; Deni Elfiati; Ahmad Baiquni Rangkut (Repong Damar: Jurnal Pengabdian Kehutanan dan Lingkungan, 2022)
The community service program for the mandatory lecturer scheme in 2021, Universitas Sumatera Utara, is foc Integrasi Agroforestri dan Sistem Budidaya Lebah Madu (Trigona Sp.) dalam Penguatan Food Estate di Humbang Hasundutan.  used at the food estate location, Humbang Hasundutan Regency. The purpose of this community service program is to develop a group of forest communities around the location of the food estate that are economically independent through the skills of honey bee cultivation of Trigona sp. in strengthening food at food estate locations. This program integrates forestry, agricultural, and honey bees Trigona sp. to form an interrelated cultivation system for the sustainability of ecological, economic, and social aspects. This program is carried out in the form of assistance in providing honey bee sires Trigona sp. and training in honey bee cultivation management. This program is expected to be able to have a positive impact on the community of food estate farmer groups as a companion business in managing food estates based on agricultural commodities.